PENGARUH MOTIVASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA ANGGOTA POLRI DI DIREKTORAT TINDAK PIDANA KORUPSI MARKAS BESAR POLISI REPUBLIK INDONESIA - Guntor, Muhamad; Ramdhan, Muhammad; Saksana, Joned Ceilendra (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
This research was conducted at the Directorate of Corruption Crimes at Bareskrim Polri, involving a population of 88 personnel. Using a descriptive method with a quantitative approach, a sample of 88 respondents was obtained with a margin of error of 5%. The objective of this study is to determine and analyze the influence of motivation and emotional intelligence on the performance of personnel at the Directorate of Corruption Crimes, Bareskrim Polri. Questionnaires were distributed to respondents using probability random sampling, and quantitative data analysis was performed using multiple linear regression analysis with SPSS 22. The partial results indicate that both motivation and emotional intelligence positively and significantly affect the performance of personnel. Simultaneously, motivation and emotional intelligence also show a positive and significant influence, with a coefficient of determination (R²) of 56.9%. Motivation and emotional intelligence variables have a dominant influence on the performance of personnel, with a constant coefficient value of 0.583. This indicates that the higher the motivation and emotional intelligence of the personnel, the better their performance at the Directorate of Corruption Crimes, Bareskrim Polri